2019
DOI: 10.3390/nu11030535
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Evaluation of a Diet Quality Index for Asian Toddlers and Its Perinatal Correlates: The GUSTO Cohort Study

Abstract: Early childhood diet may have lifelong influences on health outcomes, yet development of indices to assess diet quality is scarce in toddlers, especially in Asian countries. We aimed to develop and evaluate a Diet Quality Index (DQI) in a multi-ethnic Asian mother–offspring cohort and identify perinatal correlates of early childhood diet. Based primarily on the Singapore dietary guidelines, the DQI includes seven food components: rice, bread and alternatives; fruit; vegetables; meat and alternatives; milk and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 49 publications
5
37
1
1
Order By: Relevance
“…The HEI-SGA scores across the cohort suggested that dietary intake was frequently divergent from dietary guidelines in this cohort, with the median score of the current sample (48.5 out of 100) appearing lower than similar estimates of diet quality in Singaporean pre-teen (median 65.4 out of 100) and infants (mean 44.2 out of 65) noted in recent studies [ 34 , 35 ].…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The HEI-SGA scores across the cohort suggested that dietary intake was frequently divergent from dietary guidelines in this cohort, with the median score of the current sample (48.5 out of 100) appearing lower than similar estimates of diet quality in Singaporean pre-teen (median 65.4 out of 100) and infants (mean 44.2 out of 65) noted in recent studies [ 34 , 35 ].…”
Section: Discussioncontrasting
confidence: 54%
“…Such approaches may also be less prone to confounding factors than an evaluation of intake of single or multiple nutrients and food groups [ 33 ]. While approaches to estimate overall dietary quality have been published for Singaporean infants and children [ 34 , 35 ], the authors believe that no such method has currently been defined for late adolescents and young adults.…”
Section: Introductionmentioning
confidence: 99%
“…Anak Usia Dini memiliki Indeks Makan Sehat rata-rata hanya 60 %, dimana AUD jarang mengkonsumsi sayuran dan kacang-kacangan hijau serta tinggi konsumsi makanan lemak jenuh PAUD (Murphey et al 2011). Chen et al (2019) juga menemukan kebiasaan AUD mengonsumsi makanan jenis karbohidrat per-hari mencapai 58,1 %, makanan gula tinggi 94,8 %, sedangkan sayur hanya 9,8%, dan buah hanya 28 %.…”
Section: Pendahuluanunclassified
“…Gevers et al (2016) found that 7-12-year-old children of mothers with a lower educational level consumed more energy-dense snacks, compared to children of higher educated mothers. Likewise, studies of Durão et al (2017), Chen et al (2019), van der Velde et al (2019), and Gutiérrez-Camacho et al (2019) confirm the relation between higher maternal education and a healthier dietary pattern of their children. Whether maternal educational attainment influences mothers' snack choices for their 2-7-year-old children and the possible value conflicts experienced is studied in this thesis.…”
Section: Mothers' Educational Levelmentioning
confidence: 78%
“…Parents influence the food intake of their children through their interaction with their children, as well as by the availability of foods at home (Horst and Sleddens, 2017). In addition, the educational level of the mother is of influence on their food choice for their children (Craig et al, 2010;Chen et al, 2019;van der Velde et al, 2019;Damen t al., 2019b). Also the family structure, including the presence of siblings has been shown to influcence eating habits of children (Haines et al, 2019, Damen et al, 2020b.…”
Section: Introductionmentioning
confidence: 99%